Not for profit why democracy needs the humanities - Nussbaum, Martha Craven 1947- (Public square (Princeton, New Jersey), 2010)
"Philosopher Martha Nussbaum makes a passionate case for the importance of the liberal arts at all levels of education. Nussbaum argues that we must resist efforts to reduce education to a tool of the gross national product. Rather, we must work to reconnect education to the humanities in order to give students the capacity to be true democratic citizens of their countries and the world"--Jacket.